Tindak Tutur Ekspresif dalam Daftar Putar Maudy Ayunda’s Booklist “3 kunci Membangun Kekayaan” di Youtube - Dian Nurul Fitra; Dwi Praptiwi (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
An expressive attitude is a type of attitude that expresses something felt by the speaker. Expressive expression is understood not only through the expression but through gestures or movements performed by the communicator (source) to the communicant (receiver) to express his feelings. The purpose of this research is to find out what expressive expression Maudy Ayunda uses in her video entitled "The Three Keys to Building Wealth". The type of research used in this research is qualitative descriptive research. The data collection technique in this study uses documentation, logging, and recording techniques. The documentation on this research is a motivating video. There are five kinds of tactics that Maudy Ayunda used in the video, including non-expressive praise, condemnation, criticism, blame and gratitude. The researchers hope that the next research could dig deeper into the subject of obedience with more complex explanations with many resources that could be used..